Family Empowerment Through Digital Financial Management UP2K Sere Serumpun Jambi - Yossinomita Yossinomita; Mardiana R; Irfan Hassandi; Vina Andiliana S; Bagus Irmawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Family economic empowerment is a critical strategy for improving community welfare, particularly through household-based productive programs such as the Family Income Improvement Program (UP2K). This community service initiative aimed to strengthen the financial management capabilities of members of the UP2K Sere Serumpun group in Bagan Pete Village, Alam Barajo Subdistrict, Jambi City, Indonesia, through the adoption of digital financial management tools. The program included structured training and mentoring to equip participants with practical skills in recording income and expenses, managing savings, planning budgets, and monitoring cash flow using accessible digital applications. The implementation of digital financial management enhanced participants’ financial literacy, accountability, and confidence in managing both household and group finances, contributing to economic independence and the sustainability of small-scale enterprises. Key challenges identified included limited access to technology, varying levels of digital literacy, and initial resistance to transitioning from manual to digital systems, highlighting the importance of continuous guidance and support. This community service demonstrates that integrating digital tools into UP2K programs can significantly improve financial administration efficiency, empower households economically, and strengthen local economic resilience in the digital era.